Spontaneous fission half-life in Fm isotopes with nuclear energy density functional - Washiyama Kouhei (EPJ Web of Conferences)
A microscopic description of fission dynamics is important to understand the decay properties of neutron-rich heavy nuclei that are relevant to r-process nucleosynthesis. To provide a reliable and efficient method to evaluate the spontaneous fission half-life, we develop a method, called the constrained Hartree– Fock–Bogoliubov (CHFB) plus local quasiparticle random-phase approximation (LQRPA), to include dynamical residual effects in the collective inertia. With the CHFB + LQRPA, we evaluate the collective potential and the collective inertia along a mass-symmetric fission path in Fm isotopes with the neutron numbers N = 158–164. The obtained LQRPA inertia is much larger than the cranking one that ignores dynamical residual effects and shows a remarkable variation along the fission path. We estimate the fission half-life of the Fm isotopes using the action integral with the obtained collective potential and inertia. A large difference between the fission half-lives obtained with the LQRPA inertia and with the cranking inertia is observed. This indicates the importance of evaluating the collective inertia for estimating the fission half-life.